'Bones in the Forest' in Matabeleland, Zimbabwe: Exhumations as a Tool for Transformation. (22nd September 2014) - Eppel, Shari
Abstract 1 : The need to honour the dead is universal, and of particular importance in animist cultures, where the aggrieved dead can cause illness, crop failure, infertility and failure to marry. While the angry dead and their role in rural communities after state conflict are increasingly acknowledged in the transitional justice literature, there have been no longitudinal studies on the humanitarian outcomes and transformational possibilities of exhuming and reburying murdered civilians. Exhumations in rural Zimbabwe in the 1990s, which allowed the reburial of civilians killed in the 1980s Gukurahundi massacres, are assessed here from the vantage point of 2014. Families mostly continue to reflect on positive outcomes from the reburials. The reburials are perceived as having transformed family dynamics, healing rifts and allowing for the reintegration of alleged sell-outs. Retrospectively, it is clear that most people did not know where their relatives were until the exhumations provided a context for previously silent neighbours to tell the truth. Exhumed gravesites that were once indicative of horrific murders now signify wrongs that were put right, allowing the community to 'go there.' The potential of reburials to address the rights of the living dead needs to be more widely addressed in transitional justice policies.